The Princess Aline - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Princess Aline" by Richard Harding Davis is a novelette published in 1895. A young, wealthy American artist becomes captivated by a photograph of a European princess and embarks on a transatlantic voyage to meet her. Accompanied by companions encountered during his journey, he pursues this romantic obsession across Europe. The story blends travel narrative with whimsical romance, exploring the boundaries between social classes and the possibilities$1 (Bor impossibilities$1 (Bof love between a commoner and royalty. Davis's tale became the fifth-best selling novel in America that year. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Princess_Aline
Release date is 1995-09-01
Keywords: Young men -- Fiction; Princesses -- Fiction